Impact of Climate Change on Ecosystem Services - Satish Kumar Bhardwaj (International Journal of Economic Plants)
Climate change is one of the most important global environmental challenges in the history of mankind. The change in climate is mainly caused by increasing concentration of Green House Gases in the atmosphere. Climate of the planet earth is always in a state of change as a natural process influenced by both natural variability and induced environmental changes due to anthropogenic reasons. Moreover Climate change according to Inter Governmental Panel on Climate Change (IPCC) refers to ‘a change in the state of the climate that can be identified (using statistical tests) by changes in the mean and/or the variability of its properties that persist for an extended period, typically decades or longer. Climate change will likely put at risk many of nature’s benefits, or ecosystem services, that humans derive from our lands and waters. Climate-mediated loss or disruption of ecosystem functions are very likely to have repercussions for society’s dependence on ecosystems for wild-caught and farmed food, recreation, nutrient cycling, waste processing, protection from natural hazards, climate regulation, and other services. Ecosystem services do not vary independently of one another, and as a result, one general strategy for responding to harmful reductions in one ecosystem service is to boost another ecosystem service, or to reduce interacting stressors. Better management of supporting services in general may provide substantial adaptive capacity for the negative impacts of climate change on other services. Policies and incentives aimed at getting people to behave differently, or change the location and type of livelihoods they engage in, are urgently required. Therefore, to understand the gaps in our scientific understanding of how ecosystem services will respond to climate change is need to be emphasized.